Barry flanagan - Wallis, Clarrie; Exhibition London, tate Britain 2011-09,27 (New York, NY : Abrams, 2011)
The sculptor Barry Flanagan (1941-2009) was best known for his bronze hare sculptures that walk, leap or sit in galleries and public spaces around the world. This book brings together works from between 1965 and 1982, re-evaluating Flanagan's position as a key figure in the development of British and international sculpture
Published on the occasion of the exhibition Barry Flanagan : early works, 1965-1982 held at Tate Britain, 27 September 2011 - 2 January 2012.
boek